1973
DOI: 10.1177/030098587301000207
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxicosis in Beagle Dogs. 1. Clinical and Clinicopathological Features

Abstract: Abstunct. Rice culture of Aspergillus ochraceus that contained ochratoxin A or pure crystalline ochratoxin A was administered orally daily to 23 young male Beagle dogs. Six other young male Beagles served as controls. Most dogs were killed in extuenzis on or before day 14 after receiving a daily oral dose of ochratoxin A, 0.2-3.0 nig/kg body weight. Consistent clinical features of the mycotoxicosis were anorexia, weight loss, emesis, tenesmus, passage of clots of blood-stained mucus from the rectum, rectal tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Ochratoxin A was found to be a potent nephrotoxin in pigs, a finding that agrees with observations made in other species [13,26,30,36,371. This study indicated that ochratoxin A had an early destructive action on the renal tubular epithelium as evidenced by elevation of B U N , by glucosuria, proteinuria and changes in specific gravity and urinary sediment and, mainly by the elevations in the concentration of urinary enzymes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Ochratoxin A was found to be a potent nephrotoxin in pigs, a finding that agrees with observations made in other species [13,26,30,36,371. This study indicated that ochratoxin A had an early destructive action on the renal tubular epithelium as evidenced by elevation of B U N , by glucosuria, proteinuria and changes in specific gravity and urinary sediment and, mainly by the elevations in the concentration of urinary enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…This study indicated that ochratoxin A had an early destructive action on the renal tubular epithelium as evidenced by elevation of B U N , by glucosuria, proteinuria and changes in specific gravity and urinary sediment and, mainly by the elevations in the concentration of urinary enzymes. In pigs, as in dogs [36], urinary concentrations of GOT, LDH, and ICDH were increased and were useful in detection and evaluation of the nephrotoxicity. The renal origin of enzyme concentrations in urine is suggested by work reviewed earlier [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It see ms th at high e r dose s of citrinin o r o f t he co m bine d myc ot o xins wer e requi red to lo wer se rum pot a ssium a nd chlo r ide . Researc hers hav e reported reduced se rum e le ctro lyte co nce ntrat ions a fter g iving 3 mg/k g ochratoxin A dail y [35]. Rena l losse s of so d ium have bee n re lated to im pa ire d act ive re sorption o f so d ium aft er rena l tub ular necro sis [3 7] .…”
Section: Discussionmentioning
confidence: 99%
“…Six 8-week-old male Beagle dogs were purchased for this study (trial VII) as reported previously [37]. They were kept in individual cages in a room with environmental controls and were offered semi-moist dog food twice daily.…”
Section: Methodsmentioning
confidence: 99%